Zeolite/Cellulose Acetate (ZCA) in Blend Fiber for Adsorption of Erythromycin Residue From Pharmaceutical Wastewater: Experimental and Theoretical Study - Jodeh, Shehdeh; Erman, Israa; Hamed, Othman; Massad, Younes; Hanbali, Ghadir; Samhan, Subhi; Dagdag, Omar; Kaya, Savaş; Serdaroğlu, Goncagül (Frontiers in Chemistry, 2021)
The expanding amount of remaining drug substances in wastewater adversely affects both the climate and human wellbeing. In the current investigation, we developed new cellulose acetic acid derivation/zeolite fiber as an effective technique to eliminate erythromycin (ERY) from fluid. Because of the great number of active sites, the adsorption of ERY to the outside of the adsorbents. The number of interchangeable sites in the adsorbent structures and the ratio of ERY to the three adsorbents were identified as the main reasons for the reduction in adsorption as the initial ERY concentrations increased. Additionally, to pseudo-first-order modelling for all adsorbents, the pseudo second-order modeling showed better fitting for the adsorption. However, the findings obtained in pseudo-first-order model were still enough for explaining the sorption kinetics of ERY, showing that the surface displayed all chemi-sorption and physi-sorption adsorption processes by both adsorbents. The three adsorbents showed negative values of ΔH and these values were -6200, -8500 and -9600 KJ/mol for zeolite, CA and ZCA respectively and this shows that the adsorption is exothermic. The desorption analysis shows no substantial loss of adsorption site after three trials, indicating higher stability and resilience of the three adsorbents, indicating a strong repeatability of their possible use in adsorption without contaminating the environment. In addition, the chemical attitude and possible donor-acceptor interactions of the ERY were assesed by the quantum chemical parameters (QCPs) and NBO analysis performed, at the HF/6-311G** calculations.